Implementation Strategies of Mosque-Based Religious Moderation Pioneers in Fostering Social and Religious Harmony - Muhammad; Yunita Asman; Cholizar; Desy Sary Ayunda (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
In recent years, the issue of religious moderation has become a central concern in national religious discourse, along with increasing social polarization and the spread of extremist ideologies that potentially threaten social cohesion. Mosques, as religious institutions deeply rooted in community life, possess significant potential to serve as agents in promoting wasathiyah (moderate) Islamic values. This study aims to explore the lived experiences, perceptions, and meaning-making processes of mosque stakeholders as they implement the Masjid Pelopor Moderasi Beragama (MPMB) program in Aceh to foster social and interreligious harmony. Employing a qualitative approach with a phenomenological case study design, this research was conducted in three representative settings: Istiqamah Benuaraja Mosque in Aceh Tamiang, MAN 1 Mosque in Aceh Tenggara, and the Campus Mosque of UIN Ar-Raniry in Banda Aceh. Data were collected through in-depth interviews, participatory observation, and document analysis to uncover the subjective experiences and contextual interpretations of imams, mosque administrators, educators, and community members. The findings reveal that each mosque developed contextual strategies grounded in its experiential understanding of local community dynamics. Participants emphasized community-based approaches rooted in local wisdom, the integration of moderate religious values into formal education, and the development of digital campus-based da'wah. Despite these efforts, challenges persist, including limited conceptual literacy about religious moderation, insufficient human resources and funding, the absence of standardized training modules, and weak monitoring and evaluation systems. Theoretically, this study contributes to expanding phenomenological insights into institutional religious practices within contemporary Islamic scholarship. In practice, the findings provide a grounded basis for developing policies and training curricula on religious moderation that are more systematic and responsive to the real experiences of mosque communities.